Eksistensi dan Konsep Syifa’ dalam Tafsir Fakhrudin Al-Razi - Gista Naruliya Siswanti (LPPM Institut Pesantren KH. Abdul Chalim, 2019)
The Qur'an is a holy book of Muslims in which it discusses various things, both relating to world affairs or the afterlife. Al quran is a comprehensive book so that all problems can be found in this holy book. One of the issues discussed in the Qur'an is Syifa 'or medicine, a variety of interpreter experts examine efforts to reveal the meaning of syifa’ contained in the Qur'an, trying to understand the contents of the meaning in each Syifa word. 'One of the leaders who tried to understand this was Fakhrudin Ar Razi. This study will examine the Syifa concept 'according to Fakhrudin Ar Razi, using a qualitative approach, observing religious reference sources or literature studies that are directly related to the theme and title and focus of the researcher's research. The results of the study found that there were various words in the Qur'an which had the same meaning as Syifa 'namely Bur'ah and Salamah. In addition, according to Ar Razi, the purpose of the word Syifa 'is human, therefore Syifa’ in the Qur'an is intended as a remedy for human jism to maintain human health, heal and strengthen one's body and soul globally which is also beneficial for its environment.